Legal Protection for the Customary Community of Kampung Tua Pulau Rempang Against the Impact of the Rempang Eco-City Project in Batam City - Madaniyah Anugrah Murti; Indri Fogar Susilowati (NOVUM : JURNAL HUKUM, 2024)
The development of Rempang Eco-City in Rempang Island, Batam City is relocating the Kampung Tua indigenous community from their territory. The Kampung Tua indigenous community that occupies Rempang Island has rejected the relocation plan by the government because it has the potential to eliminate the identity of the indigenous community in its territory. The purpose of this research is to analyze legal recognition and protection with the suitability of laws and regulations on the utilization of the area given to the Kampung Tua indigenous community. This research is a normative legal research with statutory approach and concept approach. Batam Mayor Decree No.105/HK/III/2004 recognizes the area and does not recommend the designated area to be given Management Rights. Therefore, development in the area of indigenous peoples must guarantee the participation and protection of the Kampung Tua indigenous peoples. As the owner of the Management Rights, BP Batam, can utilize the land by cooperating with other parties, the Rempang Eco-City project is a development plan between BP Batam and PT MEG. Development must provide protection for customary law communities. The lack of guarantee for the participation of Kampung Tua indigenous people in the development of Rempang Eco-City and respect for the recognition of Kampung Tua's territory, has neglected the protection of indigenous people.